Unlocking meaning: Truth-conditional semantic and syntactic analysis in the Bible - Stevani, Margaret (KURIOS, 2024)
This research focused on complex conditional sentences in the Christian bible, employing truth-conditional semantics and syntactic analysis to uncover their theological messages. A qualitative study analyzed 20 verses, categorized into four types of conditional sentences according to Ferdinand de Saussure's syntagmatic and paradigmatic relations. It involved word analysis, structural classification, context correlation, synonymous exploration, and historical and theological consideration. The findings revealed several key insights. First, conditional sentences in the Christian bible predominantly featured compound-complex structures with an active voice, highlighting subjects and actions in religious verses. Second, they adhered to declarative formats, aligning with truth-telling principles in religious contexts. Third, complex structures and subordinate clauses conveyed conditional details, reasons, and situations, elaborating on the interplay between syntax and semantics. This research enriched our understanding of the relationship among verb forms, modal verbs, and diverse meanings within English conditional sentence types in the Christian bible. Fourth, this research had a significant social impact on human development from a theological perspective by enhancing spiritual growth, critical thinking, and ethical understanding. It promoted personal transformation and reflective faith, providing religious leaders with tools to interpret scripture more accurately. Additionally, the research clarified how biblical language communicated moral imperatives, supported ethical frameworks, and facilitated interfaith dialogue. Preserving theological heritage contributed to the holistic development of individuals and communities. Ultimately, this study aimed to ensure the Bible's relevance in shaping social behavior aligned with Christian teachings.